2021
DOI: 10.2147/dmso.s301352
|View full text |Cite
|
Sign up to set email alerts
|

Early Predictors in the Onset of Type 2 Diabetes at Different Fasting Blood Glucose Levels

Abstract: This study investigates the possible roles and potential prediction ability of metabolic parameters in the early development of T2D by detecting their serum levels at different fasting blood glucose (FBG) levels. Methods: The subjects were included and divided into normal glucose tolerance (NGT), prediabetes (PD), and T2Dsubgroups. Apart from detecting the levels of routine biochemical parameters, fasting serum insulin (FINS), 25(OH)D, thioredoxin-interacting protein (TXNIP), thioredoxin (TRX), and NOD-like re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…Previously, we reported changes in the level of various metabolic parameters and several physical characteristics with increasing FBG levels. 46 Here, with newly enrolled subjects, we showed similar trends in SBP, DBP, BMI, WC, WHR, TG, LDL, FPG, FINS, HOMA-IR, and HOMA-β. In addition, to further classify the subjects with prediabetes into the PD-A (5.6 mmol/L ≤ FPG < 6.1 mmol/L) and PD-B (6.1 mmol/L ≤ FPG < 7.0 mmol/L) groups, we examined HbA1c, Cr, ALT, and AST in this study.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Previously, we reported changes in the level of various metabolic parameters and several physical characteristics with increasing FBG levels. 46 Here, with newly enrolled subjects, we showed similar trends in SBP, DBP, BMI, WC, WHR, TG, LDL, FPG, FINS, HOMA-IR, and HOMA-β. In addition, to further classify the subjects with prediabetes into the PD-A (5.6 mmol/L ≤ FPG < 6.1 mmol/L) and PD-B (6.1 mmol/L ≤ FPG < 7.0 mmol/L) groups, we examined HbA1c, Cr, ALT, and AST in this study.…”
Section: Discussionsupporting
confidence: 73%
“…41,44,45 In addition, TXNIP was shown to be highly positively correlated with NLRP3, caspase-1, and IL-1b, and TXNIP was abnormally expressed as the FPG level increased, suggesting that TXNIP augments the body's inflammatory response to oxidative stress. 46 TXNIP inhibits insulin expression and glucose uptake, and insulin resistance can lead to elevated TXNIP levels in islet b-cells. 40,47 Accordingly, we speculate that IRAK-M/ TLR-related diabetes may be associated with the ROS/TXNIP signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“… 32 , 33 As the number of non-obese T2DM patients increased, studies have aimed to find a more comprehensive index for predicting T2DM. 23 , 34 Further studies have shown that the LAP index was an effective tool in predicting T2DM incidence, with the capacity to include visceral fat as well as subcutaneous fat. 12 , 19 Second, although there are several mechanisms proposed to explain high triglyceride levels in diabetes, one specifically addresses muscle-related insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The soaring prevalence of early-onset T2DM among adolescents and young adults has become a global public health threat. 29 , 30 Fully understanding this trend, and systematic identification of the characteristics of subsequent complications, is crucial for developing effective interventions. In this large, matched cohort study based on the UK Biobank, in contrast to the traditional view that early-onset T2DM mainly involves macrovascular and microvascular complications, our study initially found that the complications of early-onset T2DM extensively involved a wide range of body systems even at the very early stage of the disease, although there were shared comorbidity patterns with late-onset T2DM.…”
Section: Discussionmentioning
confidence: 99%